Construction and application of a comprehensive evaluation index system for food safety - ZHOU Yuan; XUE Rui-nan; WEI Ying; LI Ming-qi (Shipin yu jixie, 2022)
Objective: This study aimed to build a unified and standardized comprehensive food safety evaluation index system. Methods: The research status of the comprehensive evaluation index domestic and abroad system of food safety were summarized from two levels of theoretical research and practical exploration. Results: Based on the analytic hierarchy process and Delphi method, a set of comprehensive evaluation index system of food safety with 6 criteria, 24 first-level indicators and 41 secondary indicators was constructed; this set of indicators combined with relevant statistical data was used to carry out an empirical analysis of the food safety situation in various administrative districts of Tianjin. Conclusion: Practice shows that this set of indicators can effectively evaluate and compare the food safety status of various districts, and has the advantages of comprehensiveness, practicality and comparability.